Synthesis of silver-copper nanoparticles using phenolic compounds extracted from palm leaves as the reducing agent / Nurul Amal Nadhirah Mohamad - Nadhirah Mohamad, Nurul Amal (2015)
Silver-copper nanoparticles have various applications including antibacteria, catalyst, electrical conductor as well as silverware. The need to find a cost effective and less hazardous method to produce nanoparticles has lead to exploration of green synthesis using plant extract. Plants with high phenolic content are good sources of reducing agent, and palm leaves are one of them. The purpose of this research is to extract reducing agents from palm leaves through water-based extraction method and use the extract in the synthesis of silver-copper nanoparticles. The produced nanoparticles were characterized for its composition and structure. By implementing response surface methodology, a maximum total phenolic content of approximately 8 mg GAE/g of dry palm leaves was obtained from extraction of palm leaves (dried at 70 °C) for 10 minutes at 70 °C. Synthesis of silver-copper nanoparticles using equal volume of silver nitrate and copper nitrate trihydrate, both at 1 mM, and 10 % of palm leaves extract has produced spherical and monodispersed silver-copper alloy with average size of 13.0 ± 0.3 nm. Changes in the concentration of metal salt solutions and palm leaves extract as well as the volume ratio of metal salt solutions significantly affect the composition of the produced nanoparticles with minimal effect on the particle size. It is hope that this study can contribute to the less expensive and environmentally benign production of nanoparticles.